Schoology as Learning Media to Improve Students’ Writing Skill - Putu Yuni Widianingsih; Diah Ayu Manik Pradnya Dewi; Putu Enik Kristianti (English Education Department STKIP Agama Hindu Singaraja, 2021)
The development of Information and Communication Technology (ICT) offers many solutions for the teacher to use an effective learning platform to improve students’ writing skills. Schoology is a learning application that can be used by teachers and students to teach and to learn writing. This paper aims to explain the use of Schoology in teaching writing and its benefits for students’ writing skills. Literature study was used as the method of this study in collecting the data. The study found that: 1). Students who were taught by using Schoology had better writing skill than those who were not. 2). Schoology was found effective media for teaching writing due to its easiness and friendly display. The findings are expected to be an alternative learning media used by both teachers and students in supporting the teaching and learning process in writing.